PERAN PEMERINTAH DAERAH DALAM PENGELOLAAN TATA RUANG WILAYAH KABUPATEN BULUKUMBA DALAM PERSPEKTIF SIYASAH SYAR’IYAH - Angraini H, Ninda; Safriani, Andi (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
District and city governments are given authority in the implementation of spatial planning including regulation, guidance, supervision of the implementation of spatial planning of districts/cities and strategic areas of regencies and cities. This research aims to find out how the role of the Bulukumba Regency Government in the Management of Willah Spatial Planning. This type of research is field research with normative and syar’i approaches. The results showed that the role of the government in spatial planning management is carried out through the function of coordination, program preparation and implementation, preparing materials for the formulation and implementation of technical policies in the field of spatial planning for district areas and district strategy areas, conducting arrangements, supervising the implementation of spatial planning, conducting planning, and holding cooperation between regions in spatial management. In the history of Islamic rule, the concept of regional arrangement began when the Prophet and his companions emigrated to Medina, and the presence of the Prophet slowly turned Medina into a center of civilization, trade, education, and the previous government Medina was only an area that became a crossing for traders.